New-onset IgG autoantibodies in hospitalized patients with COVID-19 - Sarah Esther Chang (Nature Portfolio, 2021)
Infection with SARS-CoV2 and the development of Coronavirus disease 2019 (COVID-19) has been linked to induction of autoimmunity and autoantibody production. Here the authors characterise the new-onset IgG autoantibody response in hospitalised patients with COVID-19 which they correlate to the magnitude of the SARS-CoV2 response.